PERSEPSI TENTANG KEPEMIMPINAN KEPALA SEKOLAH DAN MOTIVASI KERJA GURU - Mangngissengi, Mangngissengi (Pascasarjana Universitas Negeri Makassar, 2013)
This research aims at describing perception on principals leadership and teachers’work motivation. Besides, this research is also conducted to examine the correlation between perception on principals leadership and teachers’work motivation. This study a quantitative research with the population of all the public junior high school teachers in Jeneponto. Samples of the research are taken in two stages, those are the school selection by using cluster randon sampling teacnique and teachers selection by using randon sampling teacnique. Data were collected through questionnaire and documentation. The data ere then analyzed by using statistic and inferential analysis (the correlationof product moment). The result of of the research shows the teachers’ perception on principals leadership tends to be on the high category and teachers’work motivation is on the average category. Where as the correlation between perception on principals leadership and teachers’work motivation show positive and significant correlation.